2018
DOI: 10.24843/metamorfosa.2018.v05.i01.p16
|View full text |Cite
|
Sign up to set email alerts
|

MDR-1 Gene 1199 Variant Primer Design Techniques in Pediatric Patient Buffy Coat Samples With Lla

Abstract: Single Nucleotide Polymorphism (SNP) 1199 dapat diidentifikasi menggunakan sampel buffy coat dengan metode Polymerase Chain Reaction (PCR). Komponen- komponen yang diperlukan pada proses PCR adalah template DNA; sepasang primer, yaitu suatu oligonukleotida pendek yang mempunyai urutan nukleotida yang komplementer dengan urutan nukleotida DNA templat; dNTPs (Deoxynucleotide triphosphates); buffer PCR; magnesium klorida (MgCl2) dan enzim polimerase DNA (Handoyo dan Rudiretna, 2001). Primer sangat mempengaruhi sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 4 publications
1
7
0
13
Order By: Relevance
“…A TM that is too low will result in the attachment of the primer to the template being non-specific. At the same time, if it is too high, it will result in an inefficient PCR product because the primer and template DNA are difficult to bind to each other [11]. This is also in line with the statement by Solanki [12] that a TM that is too low can allow the primer to attach elsewhere and produce non-specific PCR products.…”
Section: Primer Designsupporting
confidence: 68%
“…A TM that is too low will result in the attachment of the primer to the template being non-specific. At the same time, if it is too high, it will result in an inefficient PCR product because the primer and template DNA are difficult to bind to each other [11]. This is also in line with the statement by Solanki [12] that a TM that is too low can allow the primer to attach elsewhere and produce non-specific PCR products.…”
Section: Primer Designsupporting
confidence: 68%
“…The initial stage of PCR amplification is to analyze the purity and concentration of DNA, where the minimum requirement for DNA purity is 1-2 (ideally 1.8-2). Meanwhile, the concentration of DNA for DNA profiling is 20 g/ml [20]. In this study, the results of DNA purity by nanodrop from existing samples showed between 1,069 g/µl and 1,265 g/µl (data not shown), so that the DNA purity requirements to proceed to the PCR amplification stage were met so that it could be used in identification.…”
Section: Pcr Amplificationmentioning
confidence: 73%
“…If the temperature of Ta is high, then the primer and DNA template are difficult to bind so that it will produce a low (less efficient) PCR product. However, if Ta is too low, it will cause the primer attachment process to be on a non-specific template [19]. Based on the data analysis, all tables indicate that all primary candidates are included in the criteria.…”
Section: Resultsmentioning
confidence: 99%